Pertimbangan Hakim Banding Terhadap Tindak Pidana Korupsi Kredit Fiktif pada Perbankan Milik Badan Usaha Milik Negara (Studi Putusan Nomor : 16/Pid.Sus-TPK/2023/PT.Tjk) - Hartono, Bambang; Ramadan, Suta; Siregar, Michael Gabe Bryan (Journal of Law, Education and Business, 2025)
The main aim of writing this manuscript is firstly, to find out the factors that cause criminal acts of corruption based on the case in decision Number 16/Pid.Sus-TPK/2023/PT.Tjk relating to fictitious credit in BUMN (State-Owned Enterprise) banking. Second, to analyze the judge's consideration policy in handing down decision Number 16/Pid.Sus-TPK/2023/PT.Tjk against the accused perpetrator of the Corruption Crime. The research method used by the author in this manuscript namely, the Normative Juridical Approach is an approach carried out by means of literature study (Library Research) by examining, studying and examining theories, views, concepts and statutory regulations relating to the problems in writing this manuscript and an empirical approach, namely the approach which was carried out by conducting research in the field as a research object by means of observation and interviews in order to obtain descriptions and data related to the problems in this manuscript.